Developing a Home Reading Model with Print and Digital Media to Enhance Basic Literacy Among 5–6-Year-Olds: A Study in Rembang District, Indonesia - Rohmah, Siti Yomi; Utanto, Yuli; Pristiwati, Rahayu (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
This study aims to develop, validate, and evaluate the effectiveness of a home reading model designed to foster basic literacy in children aged 5–6 years. Employing a research and development approach based on the Borg and Gall model, the study followed eight stages: data collection, planning, product development, expert validation, small-scale testing, product revision, large-scale trials, and dissemination. Participants included 16 children in the small-scale trial and 43 children in the large-scale trial from several public kindergartens in Rembang Regency, Indonesia. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed using qualitative descriptive and quantitative statistical methods. The findings revealed a strong need to implement a home reading model that integrates both printed and digital media to enhance basic literacy. Media expert validation yielded a score of 95%, indicating a high level of validity and feasibility. Content validation by material experts resulted in a 73.3% score, categorized as moderately valid. Trial results showed high levels of acceptability and usability among users, and assessment outcomes indicated a 28.1% improvement in children’s basic literacy skills. The study concludes that the developed home reading model, supported by local folktale-based storybooks, guidebooks, and literacy activity sheets in both print and digital formats, is effective in improving early literacy. This model promotes school–home collaboration and offers a culturally responsive approach to early childhood education.